KEHIDUPAN ANAK BERKEBUTUHAN KHUSUS DI SLB NEGERI SELATPANJANG DESA BANGLAS KECAMATAN TEBING TINGGI KABUPATEN KEPULAUAN MERANTI (Studi Tentang Peran Keluarga Dan Guru Dalam Mengasuh Anak Tunagrahita ) - Yuni Sudinia; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research aims to know the lives of children in need of special in Special School negeriSelatpanjang, especially on mental retardation children. How daily activities carried out bythe child's mental retardation later what are the role of the family and teachers in nurturingmental retardation. This research uses qualitative research methods, descriptive. The subjectof this research is the parent of the child's mental retardation who already set previouslynumbered 5 people and teachers the mental retardation child that add up to 5 people. In thecollection of data of researchers using the techniques of observation, interview anddocumentation. A descriptive analysis of the results shows that the activity carried out bychildren of mental retardation can be largely self-sufficient, but not all children who can beindependent. From 5 subjects the study 4 of them can do her everyday personally, such aseating, bathing, dressing, even cleaning the House. It can be said to the children of her age.However, they are very weak in their learning abilities, a very slow capture power, as well asthe type of child who is quickly forgotten with the things he had learned already. From thiswe can see the role of the teacher in his unrelenting advised, educating, gives the examplealso motivate children, always repeat back an existing lessons until children can. SpecialSchool in Selatpanjang„s programs for children with disabilities especially mentalretardation is Bina Diri. The program aims so that children can take care of her ownpersonal things, like installing a buttoned shirt, combing hair, tie shoelaces and others. Theschool is indeed more emphasis and priority to the skills of its students towards 60% BinaDiri & skills, 40% of the Academy. This expected future child can live independently withoutdepending on others. Although the study is important and the main thing, but their son mentalretardation this can not be applied because the child had an IQ below average very difficultaccepting the lessons and the lessons already learned easily lost. And they could not beforced because mental retardation tend to have mood is fickle. The role of the family in theHouse is a continuation of the role of teacher in school that is paying attention to thegrowing child, help in completing the duties of teacher in schools, also provides moral andmaterial support, providing basic education and sincere religion accept all conditions of thechild born and the spiritual.Key Words: Socialization, Role, Families, Teachers, Mental Retardation Child, SpecialSchools (SLB)